Clinical analysis of second primary gingival squamous cell carcinoma after radiotherapy. (September 2018) - Fu, Xiaoyan; Chen, Shuwei; Chen, Weichao; Yang, Zhongyuan; Song, Ming; Li, Hao; Zhang, Huayong; Yao, Fan; Su, Xuan; Liu, Tianrun; Yang, An-Kui
Highlights: We collected the patients' data during the past 48 years. Among the patients in this study, 100% had follow-up into the fifth year after initial therapy. This is the first report that individually and systematically assesses the clinicopathologic characteristics and prognosis of the gingival squamous cell carcinoma after radiotherapy. To analyse these data efficiently and authentically and to effectively reduce hybrid migration, we used propensity score matching analysis. Abstract: Introduction: Clinically, we have observed that some oral cancer patients have a history of radiotherapy for head and neck cancer; we have named this condition radiotherapy-associated cancer (RAC). Gingival cancer, which is usually juxtaposed with other oral cancer subtypes, is seldom reported individually, and there are few reports on the association between the incidence of oral cancer and history of radiation therapy. Therefore, this study aimed to elucidate the clinicopathological features and prognosis of second primary gingival squamous cell carcinoma after head and neck radiotherapy. Materials and methods: The data collected included 450 patients diagnosed with gingival squamous cell carcinoma from 1964 to 2012 at Sun Yat-sen University Cancer, among whom 52 patients had a history of radiotherapy for head and neck cancer. We retrospectively analysed the differences in the clinicopathological characteristics and prognosis between sporadic gingival squamous cell carcinoma and radiation-associated gingival carcinoma, with an emphasis on gingival carcinoma. Results: Sporadic gingival squamous cell carcinoma is less likely to have more advanced T stage, and the second primary tumour is more likely to be located in the molar area of the maxillary gingiva than in the mandibular gingiva (75.6% vs 24.4%, P < 0.05). The 5-year overall survival of patients with second primary gingival carcinoma was influenced by age distribution, T classification, N classification, clinical TNM stage, histological grade and radiation history in head and neck. Mandibular gingival carcinoma was more likely to have an increased neck lymph node metastasis than maxillary gingival carcinoma ( P = 0.001), but there was no significant difference in 5-year overall survival between these two groups ( P = 0.828). The main therapy for gingiva carcinoma is surgery or comprehensive treatment based on surgery. Conclusions: Second primary gingival squamous cell carcinoma after radiotherapy demonstrated particular clinicopathologic features, such as prominent sites and TNM stage; and there was statistically significant difference in 5-year overall survival and prognosis between second primary gingival carcinoma after radiotherapy and sporadic gingival carcinoma.